PELATIHAN DESIGN THINKING DAN PROTOTYPING UI/UX UNTUK IDE STARTUP SISWA SMA - Syamsul Rijal; Aulia Rahmawati; Rezty Amalia Aras; Furqan Zakiyabarsi; Hany Alexandria; Muhammad Fachrul Salam; Yogi Hady Afrizal; Andi Jamiati Paramita; Andi Hutami Endang; Kiki Resky Ramdhani Sucipto; Widia Febriyani (Yayasan Nusantara Hasana Berdikari, 2026)
The development of digital technology has created a new ecosystem that requires young people, particularly Generation Z, to become not only passive digital consumers but also creators of innovative solutions through the startup ecosystem. An empathy-based Design Thinking approach is considered effective in producing human-centered solutions while shaping resilient, solution-oriented young entrepreneurial character. However, students at SMA SPIDI Maros still faced difficulties in understanding business idea validation and UI/UX prototype design. This community service program aimed to provide Design Thinking and UI/UX Prototyping training to support students' startup idea development while enhancing their digital literacy. The method employed a two-session training and workshop, consisting of a Design Thinking presentation and a UI/UX Prototyping workshop using Figma, implemented through four stages: identifying participant needs, designing materials, conducting the activity, and evaluation with follow-up. The program was held on 28 January 2026 and attended by 32 participants from grades 10 to 12. Evaluation results showed all indicators fell into the